Operational daily report : 14 & 16.9.43. (1943)
210th Infantry Division Operational Daily Report for Septembers 1943. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, Reel 1620, 1a, KTB no. 3, 210 Infantry Division, Folder 45787/1, first frame 000993. Translated by Major James F. Gebhardt, USA (retired)